Transformasi Komunitas Stand Up Comedy Jogja di Era Digital - Puspita Maraji's, Maria Magdalintan Kalvari (Fakultas Psikologi Universitas Sanata Dharma, 2024)
This research aims to delve into the changes occurring within the stand-up comedy community in the face of the digital transformation that has permeated various aspects of life. Through in-depth interviews with comedians and observations on various social media platforms, this study demonstrates that digital technology has become a crucial space for the development of the stand-up comedy community. Additionally, utilizing a qualitative approach, the research explores the perspectives of performers and stand-up comedy practitioners on how digital technology affects interactive processes within this community. The findings highlight the need for alignment between the use of technology and the preservation of the essence of stand-up comedy as an art form. Key factors in ensuring the success of the stand-up comedy community in the digital era include building a strong collaborative network from within the community, aligning technology with stand-up comedy, and adapting to technological changes. This research hopes to contribute to a comprehensive understanding of the dynamics of the stand-up comedy community in the digital era while providing guidelines for comedians and community managers to maximize the potential of technology in enriching the expression of stand-up comedy as an art form.